Differences in seed characteristics, germination and seedling growth of Suaeda salsa grown in intertidal zone and on saline inland - Wang, Qikang; Xu, Deliang; Yin, Benfeng; Zheng, Yueling; Guo, Xiaohong; Li, Yating; Sun, Xiyan; Wang, Lei; Wu, Nan (Frontiers in Plant Science, 2023)
The ecological restoration of saline land in the Yellow River Delta is essential for the sustainability of this region. Halophytic species, like Suaeda salsa, are critical for the restoration process. However, potential differences in traits of heteromorphic seeds collected from the intertidal zone and inland condition have been largely overlooked. The seeds were analyzed for hardness, nutrient elements, and secretions, while structural differences were observed under a stereomicroscope. Germination percentages of the different seed types and subsequent seedling growth were also recorded. Our study found that the black seeds from intertidal zone had the highest hardness when compared to the three other types of seeds. Nutrient analysis revealed that brown seeds had a higher iron (Fe) content than black seeds. Accordingly, brown seed embryos were greenercompared to their black seed counterparts due to the iron's role in chlorophyll synthesis. Our results also revealed that brown seeds secreted greater amounts of exudates than black seeds.Finally, both the intertidal brown seeds and the inland-grown brown seeds had higher germination percentages and better early seedling growth than the corresponding black seeds. The differential characteristics between dimorphic seeds and seedlings may influence their environmental adaptation in different saline environments.